Influence of the Substitutional Solute on the Mechanical Properties of Ti-Nb Binary Alloys for Biomedical Use - da Silva, Luciano Monteiro [UNESP]; Rosifini Alves Claro, Ana Paula [UNESP]; Rabelo Buzalaf, Marilia Afonso; Grandini, Carlos Roberto [UNESP] (Universidade Federal de São Carlos (UFSCar), Dept Engenharia Materials, 2012)
Titanium alloys are widely used in the manufacture of biomedical implants because they possess an excellent combination of physical properties and outstanding biocompatibility. Today, the most widely used alloy is Ti-6Al-4V, but some studies have reported adverse effects with the long-term presence of Al and V in the body, without mentioning that the elasticity modulus value of this alloy is far superior to the bone. Thus, there is a need to develop new Ti-based alloys without Al and V that have a lower modulus, greater biocompatibility, and similar mechanical strength. In this paper, we investigated the effect of Nb as a substitutional solute on the mechanical properties of Ti-Nb alloys, prepared in an arc-melting furnace and characterized by density, X-ray diffraction, optical microscopy, hardness and elasticity modulus measurements. The X-ray and microscopy measurements show a predominance of the alpha phase. The microhardness values showed a tendency to increase with the concentration of niobium in the alloy. Regarding the elasticity modulus, it was observed a nonlinear behavior with respect to the concentration of niobium. This behavior is associated with the presence of the alpha phase.
Keywords: Ti-based alloys; elasticity modulus; biomaterials